Phytosociological Status under Pink Cedar (Acrocarpus fraxinifolius Wight and Arn.) Plantations in Himachal Pradesh - Kumar, Suresh; Gupta, N. K.; Mahajan, P. K.; Shikha, Deep (Indian Forester, 2015)
The present study was carried out at four sites. The spacing of site-I was 1.5m × 1.5m; site-II: 1.0m × 3.5m; site-III: 3.0m × 3.0m and site-IV: 4.0m × 4.0m at Solan, Himachal Pradesh. The maximum species diversity and basal area (BA) of grasses and herbs (56.65 cm2/m2 ) was at site-I having lowest plant spacing, with least basal area (BA) of shrub and woody regeneration (1.16 cm2/m2 ). Lantana camara and Murraya koenigii showed there presence at all the sites among shrubs, having dominance of Lantana camara at sites-I, -III and -IV. Apluda mutica, Chloris gayana and Chrysopogon montanus were present in all the sites among different grasses and herbs, however, Apluda mutica showed dominance at site-I and -III, while, Chrysopogon montanus dominated at site-II and -IV. Bidens pilosa dominated at site-I and -IV, while Erigeron annus was present at site-II and -III among herbs. Maximum similarity (60.00 %) between site-I and -IV was observed for grasses and herbs, however, for shrubs and woody regeneration, it (80.00 %) was observed between 3.0m × 3.0m (site-III) and 4.0m × 4.0m (site-IV) spacing.